Pre-treatment neutrophil-lymphocyte and monocytelymphocyte ratios give clues about response, survival, and recurrence in diffuse large B-cell lymphoma - Demir, Burcak; Serin, Istemi; Hilmi Dogu, Mehmet (Archive of Oncology, 2022)
Background: Diffuse large B cell lymphoma is a heterogeneous tumor group consisting of large and transformed B cells that makeup 30-40% of all non-Hodgkin lymphoma. Numerous studies point out that initial parameters and posttreatment responses can be used as prognostic factors. We aimed to examine the relationship between diagnosis, clinical and laboratory parameters, treatment response and survival using neutrophil-lymphocyte and monocytelymphocyte ratios. Methods: A total of 80 patients, followed in our hematology clinic between January 2009-2019, were included in the study and were analyzed retrospectively. Results: The median value of neutrophil- lymphocyte ratio was 3.5 (0.3-50.2) and of monocyte-lymphocyte ratio was 0.3 (0.1-4.8). In the group with neutrophil-lymphocyte ratio ≥ 3.5 response rates was significantly lower and exitus rate and the bulky mass presence were significantly higher compared to the group with > 3.5 values (p < 0.05). In the group with monocyte-lymphocyte ratio ≥ 0.30, the exitus rate was significantly higher compared to group with < 0.30 values (p < 0.05). Conclusion: A statistically significant bulky mass presence was demonstrated in the population above the neutrophil-lymphocyte ratio and monocyte-lymphocyte ratio cut off. Although not considered to be sufficient alone, these parameters could be used as prognostic factors in combination with current scoring systems.